The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4103/jfmpc.jfmpc_1190_21
|View full text |Cite
|
Sign up to set email alerts
|

Study of effect of gluten-free diet on vitamin D levels and bone mineral density in celiac disease patients

Abstract: Objective: Celiac disease (CD) is a multifactorial immune-mediated enteropathy caused by a response to ingested gluten. The current available treatment for CD is lifelong gluten-free diet (GFD). This study was done to see the effect of GFD on Vitamin D levels and bone mass density in celiac patients. Methods: A prospective interventional study on newly diagnosed celiac patients was conducted in the Pediatrics department of a tertiary care teaching institute in 2 stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…In regard to pediatric case, it appears that celiac children, observing a GFD, have dietary trends similar to the corresponding healthy controls, with both celiac and non-celiac subjects having vitamin D intake below reference standards [ 80 , 81 ]. However, in two prospective studies on pediatric celiac patients, after one year or six months of GFD, respectively, a significant increase in vitamin D level was observed, which was associated or not with a decline in PTH levels [ 82 , 83 ]. Similar results were obtained in a cohort of the adult population, where patients not adhering to a GFD had lower vitamin D and BMD values at diagnosis, and higher PTH values than subjects adhering to the diet [ 84 ].…”
Section: The Role Of Vitamin D In Metabolic Syndrome Celiac Disease A...mentioning
confidence: 99%
“…In regard to pediatric case, it appears that celiac children, observing a GFD, have dietary trends similar to the corresponding healthy controls, with both celiac and non-celiac subjects having vitamin D intake below reference standards [ 80 , 81 ]. However, in two prospective studies on pediatric celiac patients, after one year or six months of GFD, respectively, a significant increase in vitamin D level was observed, which was associated or not with a decline in PTH levels [ 82 , 83 ]. Similar results were obtained in a cohort of the adult population, where patients not adhering to a GFD had lower vitamin D and BMD values at diagnosis, and higher PTH values than subjects adhering to the diet [ 84 ].…”
Section: The Role Of Vitamin D In Metabolic Syndrome Celiac Disease A...mentioning
confidence: 99%
“…Eleven articles reported the numbers of patients and controls with VitD de ciency [8,14,18,22,25,26,28,30,33,35,43] , and eight showed that 25(OH)D de ciency was more prevalent in CD patients [8,18,25,26,28,33,35,43] . In addition, ten articles reported changes in 25(OH)D levels before and after administering a GFD in patients with CD [17,23,24,28,32,[37][38][39][40][41] ,…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…However, the diet-related increase may not be sufficient to normalize VD serum levels. Verma et al, studying a group of children with newly onset CD, reported that in those with VD insufficiency (serum concentration 12–20 ng/mL) 6 months of GFD were associated with a significant increase of VD serum levels (from baseline 14.8 ± 5.39 ng/mL to 18.22 ± 5.67), but in several of them, VD levels remained in the abnormal range [ 81 ]. This seems to confirm the importance of adequate VD level monitoring in patients with CD, both at onset and during GFD.…”
Section: Vitamin D and Celiac Diseasementioning
confidence: 99%
“…However, the optimal amount of VD supplementation to reach normal VD levels in CD patients is not established. Administration of patients with VD deficiency (<12 ng/mL) who, together with the GFD, were given 60,000 IU of VD per week during the first 3 months of treatment showed a significant increase in VD serum levels (from 9.45 ± 0.45 ng/mL to 13.53 ± 1.52 ng/mL), but no case reached normal VD values [ 81 ]. However, regardless of VD levels at onset or during GFD, most of the experts recommended that VD serum level monitoring be systematically performed in all subjects with CD, regardless of age, and VD deficiency, when documented, be corrected using the suggested dosage.…”
Section: Vitamin D and Celiac Diseasementioning
confidence: 99%